Mecanismo da atividade antifúngica do fator de necrose tumoral (TNF) frente ao biofilme de Candida albicans - Alves, Anelise Maria Costa Vasconcelos (2017)
Candida albicans is a polymorphic fungus and has as main virulence factor the biofilm formation,particularly, in prosthetic materials and host surfaces of immunosuppressed patients, causing life-threatening infections. Tumor necrosis factor (TNF) is a pleiotropic cytokine that has several functions in the defense mechanisms of the host, among which promote inflammation and, consequently, inhibit the growth of microorganisms. In protozoa, TNF can affect the growth of these through their lectin domains that are spatially distinct from TNF receptors. To our knowledge, a direct TNF effect on yeasts, which lack TNF receptors, has never been reported. Thus, the present study aims to demonstrate that TNF affects the in vitro growth of Candida albicans through a mechanism independent of the TNF receptor. For this, four strains biofilm producerCandida albicans(two strong producer and two weak producer) were cultured in the presence or absence of TNF solutions. Susceptibility to TNF was evaluated using the broth microdilution method. Biofilms were grown on 96-well microtitre plates and evaluated using XTT (2,3-Bis-(2-Methoxy-4-Nitro-5-Sulfophenyl)- 2H-Tetrazolium-5-Carboxanilide) assay, optical, confocal and scanning and transmission electron microscopy.Biochemical biofilm characteristics such as protein quantification and hydrophobicity index (HI) were also evaluated.Thus,it was observed thatTNF did not alter Candida albicans planktonic growth. However, TNF dose-dependently inhibited growing but not established biofilm development, virtually halting yeast filamentation. Preincubation with the TNF antibody adalimumab but not with the immunoglobulin G coupled TNF soluble receptor etanercept blocked TNF activity. Preincubation with the carbohydrate N,N’-diacetylchitobiose, a major component of the yeast cell wall, that binds to TNF lectin domain, abrogated TNF effect against Candida albicans growing biofilm. In conclusion, this is the first demonstration of a receptor independent TNF and no mammalian cells activity, on other words, direct effect against C. albicans biofilm growth. Blockade of TNF effect by N,N’-diacetylchitobiose suggests that it is mediated via the lectin domain of the cytokine.